2020
DOI: 10.23887/jet.v4i3.25552
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Mathematics Critical Thinking Skills through Problem Based Learning Assisted with Concrete Media

Abstract: In learning mathematics, students are still found to have difficulty in understanding and developing critical thinking skills. Therefore, the purpose of this study is to determine the significant influence of the Problem Based Learning model assisted by concrete media on the ability to think critically mathematics in grade IV in elementary school. This research was a quasi-experimental study with a non-equivalent control group design. The population of class IV SD as many as 293 people. The sample was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 11 publications
0
19
0
12
Order By: Relevance
“…Berpikir kritis ini dapat dipandang kemampuan untuk membandingkan informasi yang didapatkan oleh siswa. Selain itu kemampuan berpikir kritis juga mampu memecahkan masalah dengan benar dan tepat (Devi et al, 2016;Pramestika et al, 2020). Siswa yang memiliki keterampilan berpikir kritis juga dapat dilihat dari bagaimana siswa menghadai masalah (Chen et al, 2018;Pramestika et al, 2020;Soyadı & Birgili, 2015).…”
Section: Pembahasanunclassified
“…Berpikir kritis ini dapat dipandang kemampuan untuk membandingkan informasi yang didapatkan oleh siswa. Selain itu kemampuan berpikir kritis juga mampu memecahkan masalah dengan benar dan tepat (Devi et al, 2016;Pramestika et al, 2020). Siswa yang memiliki keterampilan berpikir kritis juga dapat dilihat dari bagaimana siswa menghadai masalah (Chen et al, 2018;Pramestika et al, 2020;Soyadı & Birgili, 2015).…”
Section: Pembahasanunclassified
“…Based on the results of the primary study selection process, we established ten primary studies consisting of four primary studies from Google Scholar (Haerani et al, 2019;Karyono & Subhananto, 2015;Primayanti et al, 2019;Soraya et al, 2018) and six primary studies from Semantic Scholar (Ahdhianto et al, 2020;Alnita & Arifin, 2017;Buana et al, 2020;Pramestika et al, 2020;Suprapto et al, 2020;Umar et al, 2020) to be used as the data in this research. 40 primary study titles from Google scholar 50 primary study titles from Semantic scholar 70 primary studies were selected based on its abstract with the detail as follow:…”
Section: Figure 2 the Selection Process Of Primary Studiesmentioning
confidence: 99%
“…Several reports related to the PBL implementation on the primary school students' MCTS in Indonesia revealed that the PBL implementation had a strong effect on the students' MCTS (Ahdhianto et al, 2020;Alnita & Arifin, 2017;Buana et al, 2020;Pramestika et al, 2020;Soraya et al, 2018;Suprapto et al, 2020;Umar et al, 2020). On the other side, some similar reports revealed that the PBL implementation had a moderate effect on the students' MCTS (Haerani et al, 2019;Karyono & Subhananto, 2015;Primayanti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Critical thinking skills are the ability to analyze facts, convey ideas, defend opinions, make comparisons, draw conclusions and evaluate the arguments given, and the ability to solve problems (Pramestika et al, 2020;Rati & Rediani, 2020). Critical thinking is one's cognitive skill to state something with confidence because it is based on logical reasons and substantial evidence (Meilana et al, 2020) and related to the students' skill to deal with everyday problems (Odebiyi & Odebiyi, 2021) by providing opportunities for students to use information sources to generate solutions and build relationships (Polat & Aydın, 2020).…”
Section: Introductionmentioning
confidence: 99%